Optimization of Shoulder Ultrasound Examination Using a Gel-Based Supplementary Applicator - Fiddinillah Fiddinillah; Edy Susanto; Dwi Rochmayanti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Air gaps between the probe and the skin surface can produce shadowing artifacts in the presented image. With the help of gel pad Artefact Shadowing can be minimized. However, in ultrasound examination Shoulder ultrasound examination performed with the patient sitting, it is possible that the gel pad is not stay consistently on the examined area. This is due to the pull of the earth's gravity, so the gel pad sheet model is still less supportive for this examination. support for this examination. The aim of this study was to develop a product design in the form of a Gel-based auxiliary applicator to optimize the examination of the Shoulder ultrasound examination, which has been tested for function based on the aspects of comfort and quality of quality of the resulting image. The Research and Development study was conducted with a multidimentional approach, resulting in a product that was tested for comfort by sonographers and tested for comfort by sonographers and image quality by radiologists. interpretation of radiologists. Data processing was done by conducting comparison of ultrasound examination of Supraspinatus Tendon in patients with body weight below 18.5 based on BMI calculation by using standard gel and by using the product, 30 samples each. The product design consists of gel pad and silicon rubber RTV-48. With the composition of the gel pad is gel wax and paraffin (5% of gel wax). Where silicon is designed with a thickness of 2 mm resembling the thickness of human skin. Product test results obtained that the comfort aspect is more optimal with the product than without using the product.